Estudo das transições estruturais na proteína crambina - Almeida, José Carlos Barros de (2019)
Structural phase transitions on polymers have been intensively investigated due to the relevance for potential technological (new materials) and biological (proteins) applications. The approaches used in these studies cover a broad range of techniques, since experimental manipulation of proteins until purely theoretical methods, including computer simulations. In spite of the complex structure of a real macromolecule, some general aspects of the phase transitions can be caught even considering coarse-grained models. For example, in a first approximation, one can classify the 20 types of amino acids into two groups according to their hydrophobicity. In this case, one has the H − P (hydrophobic - polar) model. Another possibility is to include a neutral class, originating the H0P model. In this work we also take into account electrostatic interactions between polar residues (amino acids), so the monomers are classified as hydrophobic (H), positive (P), negative (N), and neutral (X). We focus on the analysis of structural phase transitions of the protein Crambin, which is modeled here by an HPNX sequence of 46 monomers. The residues are restricted to occupy the vertices of a three-dimensional cubic lattice. Relevant physical quantities, such as energy and specific heat, are obtained through Monte Carlo simulations by means of the Pruned-Enriched Rosenbluth Method (PERM)